The Developing an Attitude Assessments Instrument and Pancasila student profiles in Islamic Religious Education Subject - Arrosyid, Muhammad Salman; Fakhruddin, Fakhruddin; Elmubarok, Zaim (Universitas Negeri Semarang, 2022)
The development of an attitude assessments instrument and Pancasila student profiles or Pancasila student profiles in Islamic Religious Education subject was a kind of Research and Development (R&D) with the objectives of: types of assessments, characteristics, validity, and reliability of the attitude assessments instrument and Pancasila student profiles in Islamic Religious Education subject at SMA Negeri 1 Buay Madang with 165 respondents. It used a Borg and Gall model modified using a Djemari Mardapi model with 8 steps, namely determining instrument specifications, creating instruments, defining instrument scales, deciding assessment systems, analyzing the instrument, instrument revision, conducting the assessments, and interpreting the results of the assessment. Here, the instrument validity and reliability were analyzed using the formula of Aiken V and Hyot. For the construct validity, Exploratory Factor Analysis (EFA) was used, while for estimated reliability, Cronbach’s alpha was employed. Based on the field tests, this instrument has been valid and reliable. In terms of data analysis of 165 respondents, 12.7% obtained low score, 80% obtained medium score, and 7.3% obtained high score. In addition, the instrument validity got the average of 0.80%, while the estimated reliability calculation using Ebel formulae gained the value of Rxx coefficient of 0.97. Moreover, the instrument reliability gained 0.80 based on the Cronbach alpha. In conclusion, the development of an attitude assessments instrument and Pancasila student profiles can provide fruitful benefits and contributions to students to be long-life learners who have global competencies and act based on Pancasila values.